2006
DOI: 10.1505/ifor.8.4.417
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of sample-based estimators of tree species richness in two wet tropical forest compartments in Panama and India

Abstract: International audienceWe assessed the performance of ten incidence-based estimators of tree species richness in simulated simple random sampling with fixed-area plots. Stem diameter-limited tree species and location data came from two species-rich wet tropical forest compartments in Panama and India. Lower limits of stem diameter were 1 cm and 30 cm, respectively. Estimators varied widely in their estimates of richness and their rankings changed frequently across sites and sample designs. A gamma-Poisson estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…They focused on the bias, precision and accuracy of the seven jackknife estimators (Brose et al, 2003). Magnussen et al (2006) evaluated the generalized jackknife estimator, which is a linear combination of conventional jackknife estimators (Sharot, 1976). Chao (1987) found that the jackknife estimators were severely negatively biased for small sample sizes but performed better with increasing sample size.…”
Section: Jackknife Species Richness Estimatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…They focused on the bias, precision and accuracy of the seven jackknife estimators (Brose et al, 2003). Magnussen et al (2006) evaluated the generalized jackknife estimator, which is a linear combination of conventional jackknife estimators (Sharot, 1976). Chao (1987) found that the jackknife estimators were severely negatively biased for small sample sizes but performed better with increasing sample size.…”
Section: Jackknife Species Richness Estimatorsmentioning
confidence: 99%
“…Only few, though, have focused on evaluation and application of the estimators to tree species from forest inventories (Chazdon et al, 1998;Condit et al, 1996;Hellmann and Fowler, 1999;Magnussen et al, 2006;Palmer, 1990Palmer, , 1991Schreuder et al, 1999). www.elsevier.com/locate/foreco Walther and Moore (2005) gathered an extensive list of additional studies and summarized them by the species richness estimators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we estimate the sampling variance of six estimators of richness, among which the second-order jackknife [28,60] and two estimators by Chao have enjoyed some popularity in studies of forest tree species richness [23,27,35,37,38,49,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of estimating forest tree species richness -at a given point in time -from species incidence data obtained from a probability-sample with fixed-area forest survey plots (quadrats), the analyst now has a choice of estimators with anticipated good performances provided the sample size is adequate (Magnussen & Boudewyn, 2008;Magnussen, Péllisier, He, & Ramesh, 2006;Magnussen, Smith, Kleinn, & Sun, 2010). The situation is different when it comes to estimation of change in richness since studies on the performance of estimators of temporal change in species richness have been lacking.…”
Section: Introductionmentioning
confidence: 99%